An existence result for sign-changing solutions of the Brézis–Nirenberg problem. (October 2018) - He, Tieshan; Zhang, Chaolong; Wu, Dongqing; Liang, Kaihao
Abstract: We consider the Brézis–Nirenbergproblem: − Δ u = | u | 2 ⋆ − 2 u + λ u in Ω